Motivations, barriers and experiences of participants in an HIV reservoir trial - Marie-Angélique De Scheerder; Ward P.H. van Bilsen; Melissa Dullaers; Javier Martinez-Picado; Udi Davidovich; Linos Vandekerckhove (Elsevier, 2021)
Objectives: We aimed to investigate the motives, barriers and experiences of HIV-STAR study participants. The HIV-STAR study was an analytical HIV treatment interruption trial (ATI) aiming to evaluate the origin of viral rebound, conducted in Ghent, Belgium. Methods: A mixed-method study was performed among 11 participants of the HIV-STAR study. Two self-administered questionnaires with 32 and 23 items, respectively, assessed motives, barriers and experiences of the research participants. In-depth interviews were conducted to further explore and understand topics that had emerged from these surveys. Results: Motives of ATI study participants were primarily related to the improvement of their own health perspectives and to their contribution to find an HIV cure. Barriers for ATI participation mostly related to practical issues, such as difficulty in planning study visits. Ten out of 11 participants reported a very high overall satisfaction and were willing to participate in another ATI. This satisfaction was predominantly linked to clear communication and guidance. Invasive sampling during the ATI was less of a burden than anticipated by participants. However, most participants underestimated the emotional impact of HIV treatment interruption, which was associated with feelings of uncertainty and loss of control. Risk of HIV transmission because of viral rebound was also mentioned as burdensome during this phase. Conclusions: Involvement in an ATI was positively evaluated by HIV-STAR participants. Contributing to HIV cure research outweighed the burden of study participation for most participants. The latter aspects were attenuated by mutual decision making and the experience of empathy from the research team. Still, issues regarding privacy and the psychosocial impact of treatment interruption, including sexuality and HIV transmissibility, should be addressed in a better way.